Estabilización de Tres Bebidas Ancestrales elaboradas con Preparados Enzimáticos. - Arias Molina, Carla Yulisa (2020)
There are different stabilizers that can be used in ancestral beverages (white chicha, black chicha and wiwis chicha) made with enzymatic preparations, however in this research issues were detailed, where stabilization as such was emphasized, since it is a very characteristic important so that there is no formation of precipitates, sedimentation, phase separation and even unwanted turbidity within ancestral beverages. For this, the primary objective was to compile bibliographic information in previously carried out projects, about the stabilizers that can be incorporated into ancestral beverages made with enzymatic preparations, and at the same time the optimization methods by which the stabilization of these drinks. To comply with these objectives, comparative tables were made where it was observed that the types of stabilizers that can be incorporated into ancestral beverages made with enzymatic preparations are xanthan gum in a concentration of 0.1% and powdered albumin in a concentration of 10 %, also emphasizing that the most optimal method according to the comparative table about the optimization methods by which the stabilization process would be carried out is through the rapid pasteurization method, that is, at a temperature of 90 ° C for 15 an 20 seconds, this process is carried out in order to eliminate the greatest amount of pathogens, and obtain a quality final product that, above all, is in accordance with the parameters established according to the Ecuadorian Technical Standard INEN NTE 2262: 2003 Alcoholic beverages , in addition to giving an important contribution to the research, scientific and technological development of future projects as well as rescuing and preserving vary the culture and traditions of the peoples where these ancient drinks still prevail intact as custom, tradition and culture of their ancestors.